Are external shocks responsible for the instability of output in low income countries? - Raddatz, Claudio E., 1973- 1973- (Policy research working paper, 2005)
"External shocks, such as commodity price fluctuations, natural disasters, and the role of the international economy, are often blamed for the poor economic performance of low-income countries. The author quantifies the impact of these different external shocks using a panel vector autoregression (VAR) approach and compares their relative contributions to output volatility in low-income countries vis-is internal factors. He finds that external shocks can only explain a small fraction of the output variance of a typical low-income country. Internal factors are the main source of fluctuations. From a quantitative perspective, the output effect of external shocks is typically small in absolute terms, but significant relative to the historic performance of these countries. "--World Bank web site